More public goods, more political reciprocity? Evidence from a post-conflict economy (2023)
While a large literature defines and diagnoses the effects of weak institutions, much less is known about how to improve them. In developing countries, there are often many signs of weak institutions that undermine reciprocal behavior between the population and the state. This paper studies the effect of community-driven post-conflict development programs in Colombia (called PDET) on citizen's reciprocal behavior, especially tax compliance and participation in social mobilization. To the extent that PDET affects these outcomes, I document the extent to which these type of programs improve state capacity. Using a difference-in-differences strategy, I compare municipalities with a close probability of being treated with treated ones to estimate causal effects. The results (due to data restrictions) show a short-term increase on protests fostered by weak institutions characteristics of the treated municipalities. On the other hand, tax revenue is influenced by an upsurge in property and sales taxes. This effect may be attributed to factors related to tax compliance, but it is not the sole plausible explanation. This provides evidence on how governments can generate new relationships on state capacity and tax compliance with historically harmful pasts societies.